Historical simulations of temperature and precipitation from the CORDEX Africa model in the Wabi Shebele Basin - Sisay Guta Alemu; Chala Hailu Sime; Tamene Adugna Demissie (Environmental Research: Climate)
Rising global temperatures and shifting precipitation patterns have significant socio-economic consequences if not properly studied and predicted. Regional climate models (RCMs) are utilized to assess local-scale climate change. However, the reliability of individual models must be validated due to inherent limitations and methodological constraints. This study evaluates the performance of CORDEX Africa RCMs using observed rainfall and air temperature data from 1986 to 2005. Model performance was evaluated using statistical indicators such as bias, RMSE, r , MAE, and a concise plot of the statistical indicators which is Taylor’s diagram. In rainfall simulation, the RACMO22T performed admirably in the upper parts of the basin (region of high rainfall and cold temperature) and lower regions of the basin (region of low rainfall and hot temperature) with bias −8.64% and 6.19% respectively. HIRHAM5 and CCLM4-8 simulate well the maximum temperature in the upper parts with biases of (0.14 °C and −0.14 °C respectively), whereas RCA4 is well performed in the lower parts of the basin. CCLM4-8 is good for minimum temperature simulation in the upper parts, but HIRHAM5 and RCA4 are good in the lower parts of the basin. In rainfall simulation, all models are slightly good in dry months than in wet. All models underestimated the maximum temperature and overestimated the minimum temperature in the study area as compared to the observed.